The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1542/hpeds.2019-0228
|View full text |Cite
|
Sign up to set email alerts
|

Refusal of Intramuscular Vitamin K by Parents of Newborns: A Review

Abstract: In 2019, the American Academy of Pediatrics made public education about intramuscular vitamin K administration at birth a public health priority, partly in response to reports of refusal of intramuscular vitamin K by parents of newborns that led to vitamin K deficiency bleeding (VKDB). We reviewed the literature on the frequency of, reported reasons for, and factors associated with refusal of intramuscular vitamin K, incidence of VKDB in newborns who did not receive intramuscular vitamin K, and use of oral vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 61 publications
2
19
2
3
Order By: Relevance
“…Loyal et al reported that the refusal of IM vit K by parents was notably higher among home births and in birthing centers. The main reasons for refusal were: concern of pain and harm from the injection and a desire to be natural and a belief in alternative methods of prophylaxis [63]. There are many factors contributing to determine an optimal vit K administration regimen e.g., cost, accessibility, compliance, ease of use, effectiveness, contra-indication, side-effects, parental refusal, or health care organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Loyal et al reported that the refusal of IM vit K by parents was notably higher among home births and in birthing centers. The main reasons for refusal were: concern of pain and harm from the injection and a desire to be natural and a belief in alternative methods of prophylaxis [63]. There are many factors contributing to determine an optimal vit K administration regimen e.g., cost, accessibility, compliance, ease of use, effectiveness, contra-indication, side-effects, parental refusal, or health care organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the USA with nearly 4,000,000 births yearly [19] and an arbitrarily estimated incidence of 2% for lack of vitamin K administration at birth, 60-70 examples of this serious example of VKDB would be expected yearly. Notably the incidence of classic VKDB is approximately 20-fold higher than that for late VKDB [18], and thus as many as 1400 of this significant, but less serious form could be expected [18]. It can be expected, as recent experience indicates (see earlier), that clusters of cases of VKDB would occur in regions with higher proportions of births at out-of-hospital sites.…”
Section: Why a Resurgence Of Late Vkdb?mentioning
confidence: 94%
“…The reasons for parental decline of vitamin K have been studied worldwide, with very similar results [15][16][17][18][20][21][22][23][24][25][26][27][28]. The principal concerns generally cited are: (1) increased risk of cancer, especially childhood leukemia (not supported by available data);…”
Section: Reasons For Refusal Of Vitamin Kmentioning
confidence: 97%
See 1 more Smart Citation
“…Increasingly, reports are being published of parents refusing vitamin K prophylaxis for their newborns. A number of reasons have been cited for this such as parental beliefs, mistrust in the medical profession or a lack of specific knowledge . Occasionally, healthcare providers do not offer the prophylaxis.…”
mentioning
confidence: 99%